(untitled) (Fiep Bulletin - online, 2017)
The greater the diversity of body movements is worked in children, the better their motor repertoire in adulthood will be,which will culminate with numerous benefits of both motor and intellectual order. Therefore, the Physical Education professional canuse swimming as a tool for assisting the development of motor coordination in children. Objective: Evaluating the motor coordinationof children that practice and don’t practice swimming. Materials and Methods: The instrument used to collect the data was the BodyCoordination Test for Children KTK (Körperkoordinationstest Für Kinder). The sample consisted of 30 children, ages between 9 and10 years (mean 9.5 ± 0.70), practitioners and non-practitioners of swimming, both genders, duly registered to two private educationalinstitutions in the city of Manaus/AM/Brazil. Results: The results showed no significant differences between the 2 groups surveyed:the group of non-swimmers showed an average Motor Quotient (MQ) of 60.46, while the group of swimmers showed an average MQof 46.93. Interestingly, the results found in swimmers students proved to be unsatisfactory, with low level of coordination, although thisgroup exercises regularly. Conclusion: It was concluded that the group of swimmers showed results below the group of nonswimmersfor motor coordination, according to KTK test. Therefore, it is suggested that other instruments are applied to these groups,as well as to others, in order to investigate the reason for these results.